2018
DOI: 10.1097/md.0000000000011710
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid annular displacement measured by 2-dimensional speckle tracking echocardiography for predicting right ventricular function in pulmonary hypertension

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…In our study, measurement of 2D-STE parameters showed a high degree of reliability. The intra and inter observer ICC for RV-LSF were excellent (both >0.93) in accordance with previous studies 27 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, measurement of 2D-STE parameters showed a high degree of reliability. The intra and inter observer ICC for RV-LSF were excellent (both >0.93) in accordance with previous studies 27 .…”
Section: Discussionsupporting
confidence: 91%
“…Ten out of 29 patients (34%) had RV dysfunction (defined by RV-FAC<35%). RV-LSF (15 [11-20] % vs 25 [21-29] %; p=0.002) and TAD lat (13 [11-20] mm vs 21 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 mm, p=0.008) were significantly decreased in the RV dysfunction group. No difference was found between the 2 groups for 2D-strain parameters, TAPSE (22 [20-25] mm vs 24 [21-26] mm;p=0.28) and RV-S’(14 [13-19] cm.s −1 vs 18 [13-20] cm.s −1 ; p=0.77) ( Appendix 2 ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations